CANADIAN POLICE KNOWLEDGE NETWORK TRAINING THE POLICE AND SECURITY PROFESSIONALS IN THE PROFESSIONAL DEVELOPMENT FOR POLICING - Barrington Duffy (The Journal of Intelligence, Conflict and Warfare, 2024)
On November 14, 2023, Barrington Duffy, Business Development Representative for the Canadian Police Knowledge Network (CPKN), presented Training the Police and Security Professionals in the professional development for policing for this year’s West Coast Security Conference. The key points discussed were the role of CPKN in training policies and professional development in policing, the issues and key focuses of the policing sector in Canada, and the need for ongoing investment in technology, collaboration, and education in overcoming challenges in the policing sector.